Molecular Phylogeny of Chuquiraga (Asteraceae-Barnadesioideae): Infrageneric Classification and Generic Affinities - Padin, Ariana Lucía (2015)
Chuquiraga is a genus of evergreen shrubs endemic to the arid and semiarid regions of the Andes and southern South America. The genus has been classified into two sections based on its variation in leaf morphology: Chuquiraga and Acanthophylla. Within section Chuquiraga, two series, Chuquiraga and Parviflorae, have been recognized taking into account variation in size of flower heads. The objectives of this study were to test this classification and to assess the monophyly of Chuquiraga and its intergeneric relationships regarding the closely related genera Doniophyton and Duseniella. The phylogenetic relationships of 24 of the 27 species and/or subspecies of Chuquiraga (19 of its 22 recognized species), plus 14 species representing seven of the remaining eight genera of Barnadesioideae, and two species of non-barnadesioid Asteraceae were inferred using sequence data from the chloroplast DNA psbA-trnH, rps16-trnK, trnL-rpl32 and/or nuclear ribosomal DNA ITS regions. The plastid and nuclear data sets were analyzed individually and combined, using maximum parsimony, maximum likelihood and Bayesian inference methods. The phylogenetic results show that Chuquiraga, Duseniella and Doniophyton form a wellsupported monophyletic group, but the relationships among these genera and the monophyly of Chuquiraga are still uncertain. The phylogenies obtained support the monophyly of the sections and reject the monophyly of the series. Section Chuquiraga is divided into two subclades: one includes all species of Chuquiraga series Parviflorae, plus Chuquiraga calchaquina and C. longiflora (of Chuquiraga series Chuquiraga), and the other subclade includes all remaining species of Chuquiraga series Chuquiraga.